APLIKASI PUPUK ORGANIK DAN ANORGANIK PADA PERTUMBUHAN ANGGREK Dendrobium indonesia damai >< violaceaflavens UMUR 7 BULAN - Karuna Dwi Mandari (JURNAL VIGOR, 2025)
Frequency and fertilizer formulation play an important role in vegetative growth of Dendrobium indonesia damai violaceaflavens. Orchid Dendrobium indonesia damai x violaceaflavens in the vegetative phase of 7 months of age. The study was conducted at the Nambangan Orchid Garden, Sidomulyo Village, Candimulyo District, Magelang Regency, Central Java from January to March 2022. The research method used a completely randomized block design with two factors. The first factor is the frequency of fertilization 4 times fertilization, 8 times fertilization and 12 times fertilization for 8 weeks. The second factor is a fertilizer formulation of 0 ml/l, AB Mix 10 ml/l, POC 18 ml/l and POC 18 ml/l + AB Mix 10 ml/l. The results showed that the frequency of fertilization had a significant effect on the increase in the number of shoots per plant. The fertilizer formulation had a very significant effect on increasing plant height and increasing the number of shoots per plant. The interaction between the frequency and formulation of fertilizer application has a very significant effect on the increase in plant height. Keywords: vegetative, Dendrobium, frequency, formulation, fertilizer.